Simple microcantilever release process of silicon piezoresistive microcantilever sensor using wet etching - Ab Rahim, Rosminazuin; Bais, Badariah; Yeop Majlis, Burhanuddin (Trans Tech Publications Ltd., Switzerland, 2014)
In this paper, a simple microcantilever release process using anisotropic wet etching is presented. The microcantilever release is conducted at the final stage of the fabrication of piezoresistive microcantilever sensor. Issues related to microcantilever release such as microscopic roughness and macroscopic roughness has been resolved using simple technique. By utilizing silicon oxide (SiO2) as the etch stop for the wet etching process, issues related to microscopic roughness can be eliminated. On the other hand, proper etching procedure with constant stirring of the etchant solution of KOH anisotropic etching significantly reduces the notching effect contributed by the macroscopic roughness. Upon the completion of microcantilever release, suspended microcantilever of 2µm thick is realized with the removal of SiO2 layer using Buffered Oxide Etching (BOE).